Gymnothorax odishi sp. nov. (Muraenidae: Muraeninae), a short brown unpatterned moray eel from Bay of Bengal, India - Mohapatra, Anil; Mohanty, Swarup Ranjan; Smith, David G.; Mishra, Subhrendu Sekhar; Roy, Sanmitra (Zootaxa, 2018)
Gymnothorax odishi sp. nov., a new short brown moray eel, is described here on the basis of eleven specimens collected from Gopalpur, Odisha, along the east coast of India, Bay of Bengal. The species is characterized with dorsal-fin origin before gill opening, jaw pores with dark rim, small black patch just behind the eye of about eye size or more, gill opening with dark rim, two branchial pores, predorsal vertebrae 4, preanal vertebrae 55–58 and total vertebrae 133–138, three large fang like median intermaxillary teeth, uniserial maxillary and vomerine teeth. The new species is compared with all short brown unpatterned moray eels known from the world.